Analysis of the Effect of Pavement Conditions on Vehicle Speed - Sekar Ayu Kusumawardhani; Nuzul Barkah Prihutomo; Danang Eko Saputro (POLITEKNIK NEGERI JAKARTA, 2022)
The Jakarta Outer Ring Road (JORR) Toll Road is a logistics route that acts as an essential transportation artery to facilitate logistics distribution. This toll road connects strategic locations to support logistics distribution. It can lead to the repetition of traffic loads, causing a decrease in the pavement quality marked by road damage. Road damage that occurs can reduce the level of safety and comfort of road users. To minimize accidents due to road damage, road users will drive their vehicles at lower speeds in locations/segments that have damage. In the study, the level of road damage was analyzed using the Pavement Condition Index (PCI) method. Vehicle speed using the time mean speed method and then statistically analyzed using linear regression using SPSS v.26 software to determine how much influence road pavement conditions have on vehicle speed. Based on the results of the analysis on the Jakarta Outer Ring Road (JORR) KM 35+000 – 45+000 toll road, the pavement conditions of the toll road are in the good category with various vehicle speeds for each group with a range of 44.80 km/hour to 79,98 km/hour and the effect of pavement conditions on vehicle speed is 51.6% for class 1 vehicle, 58,1% for class 2 vehicle, 42,2% for class 3 vehicle, 42,9% for class 4 vehicle, 44,8% for class 5 vehicle.